Health-related quality of life, depression, and self-esteem in adolescents with leprosy-affected parents: results of a cross-sectional study in Nepal - Yamaguchi Nobuko; Poudel Krishna C; Jimba Masamine (BMC, 2013)
Abstract Background Leprosy is a chronic infectious disease that has an impact on the Health-Related Quality of Life (HRQOL) of sufferers as well as their children. To date, no study has investigated the effects of parental leprosy on the well-being of adolescent children. Methods A cross-sectional study was conducted in the Lalitpur and Kathmandu districts of Nepal. Adolescents with leprosy-affected parents (n = 102; aged 11-17 years) and those with parents unaffected by leprosy (n = 115; 11-17 years) were investigated. Self-reported data from adolescents were collected using the Kinder Lebensqualität Fragebogen (KINDLR) questionnaire to assess HRQOL, the Center for Epidemiological Studies-Depression Scale (CES-D), and the Rosenberg Self-esteem Scale (RSES). Analysis of covariance (ANCOVA) was used to compare scores between the two groups. Multiple regression analysis was conducted to explore the determinants of HRQOL for adolescents with leprosy-affected parents. Results ANCOVA revealed that the KINDLR and RSES scores were significantly lower among adolescents with leprosy-affected parents compared with unaffected parents. However, the scores of "Friends" and "School" subscales of KINDLR were similar between the two groups. The CES-D score was significantly higher among adolescents with leprosy-affected parents than for adolescents with unaffected parents. The KINDLR scores for adolescents with both parents affected (n = 41) were significantly lower than the scores for those with one parent affected (n = 61). Multiple regression analysis revealed that adolescents with leprosy-affected parents who had higher levels of depressive symptoms were more likely to have lower KINDLR scores. A similar result was seen for adolescents where both parents had leprosy. Conclusions Adolescents with leprosy-affected parents had higher levels of depressive symptoms, lower levels of self-esteem, and lower HRQOL compared with adolescents whose parents were unaffected by leprosy. Thus, mental health support programs might be necessary for adolescents with leprosy-affected parents, particularly for adolescents where both parents are leprosy-affected. Further studies with larger sample sizes are necessary to draw decisive conclusions.